Hydrogel Conjugation: Engineering of Hydrogels for Drug Delivery - Linh Dinh; Sung-Joo Hwang; Bingfang Yan (Pharmaceutics, 2025)
Background: Hydrogels are 3D networks of hydrophilic polymers with various biomedical applications, including tissue regeneration, wound healing, and localized drug delivery. Hydrogel conjugation links therapeutic agents to a hydrogel network, creating a delivery system with adjustable and flexible hydrogel properties and drug activity, allowing for controlled release and enhanced drug stability. Conjugating therapeutic agents to hydrogels provides innovative delivery formats, including injectable and sprayable dosage forms, which facilitate localized and long-lasting delivery. This approach enables non-viral therapeutic methods, such as insertional mutagenesis, and minimally invasive drug administration. Scope and Objectives: While numerous reviews have analyzed advancements in hydrogel synthesis, characterization, properties, and hydrogels as a drug delivery vehicle, this review focuses on hydrogel conjugation, which enables the precise functionalization of hydrogels with small molecules and macromolecules. Subsequently, a description and discussion of several bio-conjugated hydrogel systems, as well as binding motifs (e.g., “click” chemistry, functional group coupling, enzymatic ligation, etc.) and their potential for clinical translation, are provided. In addition, the integration of therapeutic agents with nucleic acid-based hydrogels can be leveraged for sequence-specific binding, representing a leap forward in biomaterials. Key findings: Special attention was given to the latest conjugation approaches and binding motifs that are useful for designing hydrogel-based drug delivery systems. The review systematically categorizes hydrogel conjugates for drug delivery, focusing on conjugating hydrogels with major classes of therapeutic agents, including small-molecule drugs, nucleic acids, proteins, etc., each with distinct conjugation challenges. The design principles were discussed along with their properties and drug release profiles. Finally, future opportunities and current limitations of conjugated hydrogel systems are addressed.